The British world : diaspora, culture, and identity - Bridge, Carl.; Fedorowich, Kent, 1959- (London ; Portland, OR : F. Cass, 2003)
This collection of essays is based upon the assumption that the British Empire was held together not merely by ties of trade and defence, but by a shared sense of British identity that linked British communities around the globe.
Book Cover; Half-Title; Title; Copyright; Contents; Mapping the British World; NOTES; British Emigration to the Empire-Commonwealth since 1880: From Overseas Settlement to Diaspora?; I; II; III; IV; NOTES; A New Class of Women for the Colonies: The Imperial Colonistand the Construction of Empire; I; II; III; IV; NOTES; The Welsh World and the British Empire, c.1851-1939: An Exploration; I; II; III; IV; NOTES; Revisiting Anglicisation in the Nineteenth-Century Cape Colony; I; II; NOTES.
"This group of studies first appeared as a special issue of The Journal of imperial and Commonwealth history (ISSN 0308-6534), vol. 31, no. 2, May 2003, published by Frank Cass"--Title page verso
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Great Britain -- Colonies -- History; Great Britain -- Colonies -- Emigration and immigration -- History; Great Britain -- Emigration and immigration -- History; Group identity -- Great Britain -- Colonies -- History; Commonwealth countries -- Civilization; National characteristics, British; Great Britain -- Civilization; British; Grande-Bretagne -- Colonies -- Histoire; Grande-Bretagne -- Colonies -- Émigration et immigration -- Histoire; Pays du Commonwealth -- Civilisation; Britanniques; Grande-Bretagne -- Civilisation; HISTORY -- World; British; British colonies; Civilization; Emigration and immigration; Group identity; National characteristics, British; Commonwealth countries; Great Britain; Emigratie; Culturele identiteit; Nationale identiteit; Electronic books; History